Expression of DENDRIN in several glomerular diseases and correlation to pathological parameters and renal failure - preliminary study - Maja Mizdrak; Katarina Vukojević; Natalija Filipović; Vesna Čapkun; Benjamin Benzon; Merica Glavina Durdov (BMC, 2018)
Abstract Background In glomerular injury dendrin translocates from the slit diaphragm to the podocyte nucleus, inducing apoptosis. We analyzed dendrin expression in IgA glomerulonephritis and Henoch Schönlein purpura (IgAN/HSP) versus in podocytopathies minimal change disease (MCD) and focal segmental glomerulosclerosis (FSGS), and compared it to pathohistological findings and renal function at the time of biopsy and the last follow-up. Methods Twenty males and 13 females with median of age 35 years (min-max: 3-76) who underwent percutaneous renal biopsy and had diagnosis of glomerular disease (GD) were included in this retrospective study. Fifteen patients had IgAN/HSP and eighteen podocytopathy. Control group consisted of ten patients who underwent nephrectomy due to renal cancer. Dendrin expression pattern (membranous, dual, nuclear or negative), number of dendrin positive nuclei and proportion of dendrin negative glomeruli were analyzed. Results In GD and the control group significant differences in number of dendrin positive nuclei and proportion of dendrin negative glomeruli were found (P = 0.004 and P = 0.003, respectively). Number of dendrin positive nuclei was higher in podocytopathies than in IgAN/HSP, 3.90 versus 1.67 (P = 0.028). Proportion of dendrin negative glomeruli correlated to higher rates of interstitial fibrosis (P = 0.038), tubular atrophy (P = 0.011) and globally sclerotic glomeruli (P = 0.008). Dual and nuclear dendrin expression pattern were connected with lower rate of interstitial fibrosis and tubular atrophy than negative dendrin expression pattern (P = 0.024 and P = 0.017, respectively). Proportion of dendrin negative glomeruli correlated with lower creatinine clearance (CC) at the time of biopsy and the last follow-up (P = 0.010 and P < 0.001, respectively). Dendrin expression pattern correlated to CC at the last follow-up (P = 0.009), being lower in patients with negative than nuclear or dual dendrin expression (P = 0.034 and P = 0.004, respectively). Conclusion In this pilot study the number of dendrin positive nuclei was higher in podocytopathies than in inflammatory GD. Negative dendrin expression pattern correlated to chronic tubulointerstitial changes and lower CC, which needs to be confirmed in a larger series.